Perspektywy dalszego rozszerzenia Unii Europejskiej. Wybrane aspekty - Bobowski, Sebastian (Prospects of Further Expansion of the European Union. Chosen Aspects, 2008)
The European Union, compound from 27 countries presently, has to face a new challenge - membership aspirations of Turkey and Western Balkans countries. Lasting process of negotiations, without concrete conclusions so far, might be perceived as an attempt of maturity and responsibility for peaceful coexistence, economic and political cooperation of european continent, despite of so distinct disparities of individual countries.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 10, s. 182-193